1983
DOI: 10.1007/bf01398770
|View full text |Cite
|
Sign up to set email alerts
|

Quartzite corundum refractory concretes

Abstract: Quartz refractory concretes arc successfully used to line steel-casting and pig-iron ladies [1][2][3]. %~e low thermal shock resistance of these concretes does not permit their use in other heat equipment, in spite of their excellent thermomechanical properties.In the zones of the ladle lining where an inadequate amount of quartz melt is formed, the concretes do not work satisfactorily, because of spaIlatton due to temperature differences.In order to increase the resistance of the lining of steel-casting ladle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…According to UkrNIIO data, the cost of ACC is three times lower than scarce and expensive technical grade alumina [26]. In 1983In -1984 in the Western Institute of Refractories as a result of comprehensive study of various technogenic raw materials work was performed on "Technical and economic evaluation (TEE) of use of industrial waste as raw material for producing refractory materials." On the basis of the TEE the required assortment and volume of production was determined for new highly effective objects and materials based on ACC.…”
Section: Aluminochromium Catalyst Wastementioning
confidence: 99%
See 1 more Smart Citation
“…According to UkrNIIO data, the cost of ACC is three times lower than scarce and expensive technical grade alumina [26]. In 1983In -1984 in the Western Institute of Refractories as a result of comprehensive study of various technogenic raw materials work was performed on "Technical and economic evaluation (TEE) of use of industrial waste as raw material for producing refractory materials." On the basis of the TEE the required assortment and volume of production was determined for new highly effective objects and materials based on ACC.…”
Section: Aluminochromium Catalyst Wastementioning
confidence: 99%
“…The most significant volume of research in this area was carried out by the branch industries of the Ural region: UralNIIstromproekt [29], VoctIO [30], BashNIPIstrom [31], etc. In spite of the adequate scientific and technological level of the research, possibilities of using electrocorundum slag in manufacture from many forms of product, it has not been 90 V. A. Perepelitsyn et al found industrial scale application.…”
Section: Abrasive Production Corundum Slurriesmentioning
confidence: 99%